Effects of food safety standards on the livelihoods of actors in the Nile Perch value chain in Tanzania - Reuben M. J. Kadigi; Ntengua S. Y. Mdoe; Ephraim Senkondo; Zena Mpenda (Danish Institute for International Studies (DIIS), 2007)
Exports of non-traditional products from developing to developed countries have increased rapidly over the past two decades. However, one of the major challenges facing developing countries in seeking to maintain and expand their share of global markets is stringent food-safety requirements in industrialized countries. The effects of compliance with these requirements and their distributional impacts among actors in developing countries are generally not well known. Based on this understanding, a study was conducted on the Tanzanian side of Lake Victoria (in Mwanza and Mara regions) to evaluate the effects of food-safety standards on the livelihoods of actors in the Nile perch value chain using the Livelihoods Analysis and Change in Net Income (CNI) approach. The effects of food-safety standards were imputed as the residual values between the “with” and “without” compliance scenarios for a specified actor category. The results of the analysis showed that the livelihood platform and income portfolios for the “with”-compliance scenario was relatively more favourable than that in the alternative, “without”- compliance scenario. The difference in human capital and livestock holdings between fishers / crews in the two scenarios was however non-significant (P<0.05). The results of the analysis also showed that both the costs and benefits of compliance with food-safety standards were considerable. Actors in the Nile perch export supply chain (the “with”-compliance scenario) obtained the highest gross revenues and net returns, as well as incurring the highest operating costs. However, the profit margins, assets and income portfolios for most actors upstream of the fishery value chains were generally lower in both the “with” and “without” compliance scenarios than those of the actors in the subsequent stages. The overall analysis of issues in this paper suggests the need to ensure more effective and coherent planning in order to safeguard the future of the fishery sector, ensure an appropriate regulatory framework, strengthen the capacity of the stakeholders to manage the resource sustainably, develop safeguards for ensuring an equitable distribution of fishery benefits, and increase collaboration among the riparian states of Lake Victoria between them and development partners.
Keywords: 330; Lebensmittelbelastung; Einkommen; Lebensstandard; Fisch; Victoriasee; Tansania